2013
DOI: 10.1155/2013/268349
|View full text |Cite
|
Sign up to set email alerts
|

Biological Pretreatment of Rubberwood withCeriporiopsis subvermisporafor Enzymatic Hydrolysis and Bioethanol Production

Abstract: Rubberwood (Hevea brasiliensis), a potential raw material for bioethanol production due to its high cellulose content, was used as a novel feedstock for enzymatic hydrolysis and bioethanol production using biological pretreatment. To improve ethanol production, rubberwood was pretreated with white rot fungus Ceriporiopsis subvermispora to increase fermentation efficiency. The effects of particle size of rubberwood (1 mm, 0.5 mm, and 0.25 mm) and pretreatment time on the biological pretreatment were first deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…This peak range was chosen as it is least affected by chemical modification and weathering. For unmodified rubber wood, IR absorbance peaks in the fingerprint region between 800 and 1800 cm −1 were assigned to functional groups from wood biopolymers according to literature (Harrington et al 1964;Hon 1989;Pandey 1999;Pandey and Pitman 2002;Gierlinger et al 2008;Le Troedec et al 2008;Nazarpour et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This peak range was chosen as it is least affected by chemical modification and weathering. For unmodified rubber wood, IR absorbance peaks in the fingerprint region between 800 and 1800 cm −1 were assigned to functional groups from wood biopolymers according to literature (Harrington et al 1964;Hon 1989;Pandey 1999;Pandey and Pitman 2002;Gierlinger et al 2008;Le Troedec et al 2008;Nazarpour et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…have been cultivated on lignocellulose with expectation of utilizing the metabolism of the microorganism to destruct the crystallinity of cellulose and remove lignin. However, most studies were based on laboratory scales and showed limited results [26][27][28][29].…”
Section: Biological Methodsmentioning
confidence: 99%
“…Studi selanjutnya menggunakan Saccharomyces cerevisiae, efisiensi hidrolisis mencapai 80%, 85% dan 90% masing-masing untuk kelapa sawit, kayu karet dan campuran kayu keras ' (Chin et al, 2011). Selain Saccharomyces cerevisiae, mikroba jenis jamur pelapuk putih juga cukup potensial untuk perlakuan pendahuluan kayu karet secara biologi, seperti Ceriporiopsis subvermispora dan Trametes versicolor (Nazarpour et al, 2013). Pengembangan bahan yang mengandung lignoselulosa untuk produksi bioetanol masih menemui beberapa kendala.…”
Section: A Bioetanolunclassified